Junior doctors' reflections on patient safety. Issue 1037 (13th January 2012) - Ahmed, Maria; Arora, Sonal; Carley, Simon; Sevdalis, Nick; Neale, Graham
Abstract : Aim: To determine whether foundation year 1 (FY1) doctors reflect upon patient safety incidents (PSIs) within their portfolios and the potential value of such reflections for quality of care. Methods: A cross-sectional retrospective review of every 'reflective practice' portfolio entry made by all FY1 doctors within an Acute Teaching Hospital Trust was conducted in February 2010. Entries were reviewed by two independent blinded researchers to determine whether they related to a PSI that is, any unintended or unexpected incident that could have or did lead to patient harm. For all entries rated positive by both reviewers, a content analysis approach was used to code PSI into incident type, contributing factors and patient outcome according to validated frameworks developed by the National Patient Safety Agency. Results: 139 reflective practice entries were completed by 30 trainees (15 men, 15 women, mean age 24 years). Of the 139 entries, 49% reflected on a PSI. Of these, 22% were due to errors in clinical assessment; 22% were due to delayed access to care; 18% were due to infrastructure/staffing deficiencies; and 16% were due to medication errors. The most common contributing factors were team/social factors (23%), patient factors (22%), communication and task factors (both 17%). The majority of PSIs led to no harm. Six entries described PSIs resulting in patient death, the majority of which were attributable to diagnostic errors. Conclusions: FY1 doctors commonly reflect on PSIs within their professional portfolios. Such critical reflection can encourage learning but may also promote patient safety and the quality of healthcare across all medical specialties.